Mechanical transmission or dissemination of infectious pathogens/parasites by arthropods - Foil, Lane (Henry Stewart Talks, 2010)
Definition of types of transmission of agents of disease by arthropods, Indirect mechanical transmission of different agents and by different vectors, Direct mechanical transmission of different agents and by different vectors, Arthropod feeding behavior relative to transmission of different agents, Factors affecting the probability of mechanical transmission events, Ways to reduce the probability of mechanical transmission events
Reviewed at 2022/04/12